Energy efficient enhanced tree structured compression model (ET-CM) for data aggregation in wireless sensor networks - Srikanth, Nandoori; Siva ganga prasad, M (International Journal of Engineering and Technology, 2018)
Compression, is a typical strategy to decrease information measure by taking care of information excess, can be utilized as a part of postpone delicate remote sensor systems (WSNs) to diminish end-to-end bundle delay as it can lessen parcel transmission time and conflict on the remote channel. All together for remote sensor systems to misuse flag, flag information must be gathered at a large number of sensors and must be shared among the sensors. Huge sharing of information among the sensors repudiates the prerequisites (vitality effectiveness, low inactivity and high exactness) of remote organized sensor. This paper manages the investigation of compressive proportion and vitality utilization in the system by contrasting and the current compressive strategies.Â Â